Morphological Examination of the Placenta of Pregnant Women with Hypothyroidism Compared to Healthy Individuals - Hoseini, Hosnie (International Journal of Pharmaceutical & Biological Archive, 2025)
Some hormonal disorders, such as hypothyroidism, can affect the morphology of the placenta and subsequently the growth of the fetus. Objectives: This study aims to investigate the morphological changes of the placenta in pregnant women with hypothyroidism. Methods: For this case–control study, 120 fresh pairs from the labor and operation room were used. Of 120 pairs, 60 pairs belonged to the case group and 60 pairs belonged to the control group. Results: The results showed that the shape of the placenta in the case group was circular (51%), followed by oval (40%) and irregular (9%), whereas in the control group, the shape of the placenta was circular (45%), oval (32%), and irregular (23%). The average weight and thickness of the placenta in the case group were lower than those in the control group, and the surface and number of cotyledons in the case group were higher than those in the control group. Conclusion: The results of the study showed that the mother’s hormonal changes can affect the placenta, and with timely diagnosis and treatment, the effects of hormonal changes on the fetus can be prevented.